Are self-reported measures valid for the assessment of nutritional status in the brazilian population? - Raildo da Silva Coqueiro; Lucélia Justino Borges; Valbério Candido Araújo; Andreia Pelegrini; Aline Rodrigues Barbosa (Universidade Federal de Santa Catarina, 2009)
Self-reported measures have been widely used for the assessment of nutritional status in epidemiological studies. This paper discusses aspects regarding the validity of self-reported measures of body weight and height for the assessment of nutritional status in Brazilian children, adolescents, adults and elderly subjects. The available evidencesuggests that: a) in children, the use of self-reported measures is not recommended because of the lack of Brazilian studies; b) in adolescents, these measures should be used with caution since the only study carried out in Brazil was restricted to a local sample and may not represent the situation in other regions; c) in adults, this method can be considered a viable alternative for assessing and monitoring nutritional status in situations in which these data cannot be measured directly; d) in the elderly, the use of self-reported measures cannot yet be recommended for two reasons: first, studies specifically including subjects older than 60 years have not been conducted and, second, this age group tends to estimate these measures less accurately.